Accelerated corrosion test device for steel joint and experimental method thereof
Patent Information
- Application Number
- CN202611136339.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-20
AI Technical Summary
然而,该过程操作繁琐、耗时较长,且校正量过大时可能导致辅助电极过载或溶液局部过热,实施难度大,无法从根本上解决钢节点几何形态与电场均匀性之间的矛盾
本申请提供了一种钢节点的加速腐蚀试验装置,通过将中心对称钢节点固定于试验槽中心,使其分隔出多个相互连通的区域,并配合搅拌件驱动导电介质在所述多个区域之间强制循环流动,改善了离子传质分布均匀性,避免了气泡在节点表面的长时间附着,从而提高钢节点加速腐蚀试验的均匀性和结果可靠性。同时,辅助电极的对称布置有助于在节点周围建立起均匀的初始电流场,与介质流动协同作用,抑制了局部电流集中。本申请通过环绕式电极布局与钢节点自身几何形态的划分,使加速腐蚀试验装置从结构设计层面专门适配于钢节点的复杂形态,能够针对大型钢节点进行均匀加速腐蚀,操作简单便捷。
Smart Images

Figure REF-OBJ-1785230551293-000002 
Figure REF-OBJ-1785230551293-000003 
Figure REF-OBJ-1785230551293-000004
Abstract
Description
Technical Field
[0001] This invention relates to the field of corrosion testing technology, and in particular to an accelerated corrosion testing device and experimental method for steel joints. Background Technology
[0002] Corrosion is a critical issue associated with steel joints in marine engineering. In the highly corrosive marine environment, centrally symmetric steel joints exhibit a significantly higher probability of localized corrosion than uniform corrosion during service. This localized corrosion leads to stress concentration and weakens the cross-sectional strength of the components, posing a serious threat to the engineering structure. Accelerated corrosion testing using electrical current is used to study the degree of corrosion in steel joints. Compared to corrosion tests in natural marine environments, this method significantly increases the corrosion rate and shortens the testing cycle.
[0003] Most existing testing apparatuses are designed for small flat plates or regularly shaped specimens, lacking dedicated devices for steel nodes. Steel nodes possess complex geometries such as rod intersections, welds, and concave corners. In existing technologies, these complex shapes are often the cause of uneven electric field distribution and localized current concentrations. Conventional apparatuses typically employ a single pair of electrodes in a relatively opposite arrangement, concentrating the electric field along the electrode pair. The varying distances between the nodes and the electrodes make it difficult to form a uniform current field, making localized current concentrations unavoidable. Some solutions attempt to improve current distribution through iterative calibration and dynamic adjustment using multi-point potential probes, compensating for deviations by repeatedly measuring potentials and adjusting the current of each electrode. However, this process is cumbersome, time-consuming, and excessive calibration can lead to overload of the auxiliary electrodes or localized overheating of the solution, making implementation difficult and failing to fundamentally resolve the contradiction between the geometry of the steel node and the uniformity of the electric field. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide an accelerated corrosion testing device for steel nodes.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: An accelerated corrosion testing device for steel nodes includes: a test tank containing a conductive medium; steel nodes fixedly disposed inside the test tank, the steel nodes dividing the internal space of the test tank into multiple interconnected regions; auxiliary electrodes disposed inside the test tank, the auxiliary electrodes being spaced apart from the steel nodes; a power supply electrically connected to both the auxiliary electrodes and the steel nodes; and at least one stirring element disposed inside the test tank, driving the conductive medium to circulate among the multiple regions.
[0006] Optionally, the auxiliary electrode includes at least two electrodes symmetrically arranged on the inner wall of the test tank, and the height of the auxiliary electrode is not lower than the liquid level of the conductive medium.
[0007] Optionally, there are four auxiliary electrodes, distributed on two opposite inner sidewalls of the test tank, with two electrodes arranged on each sidewall.
[0008] Optionally, the steel node is a centrally symmetrical structure and is fixedly installed at the center of the test tank. The steel node naturally divides the internal space of the test tank into four interconnected quadrant regions.
[0009] Optionally, the agitator is positioned at the center of any of the quadrant regions.
[0010] Optionally, the stirring element is a magnetic stirring rotor, and the device further includes a magnetic drive element, which is disposed below the test tank and cooperates with the magnetic stirring rotor.
[0011] Optionally, the horizontal distance between the magnetic drive and the power source is not less than 0.5m.
[0012] Optionally, an insulating pad is provided between the steel node and the bottom of the test tank, and a channel for the conductive medium to flow is left between the steel node and the bottom of the test tank.
[0013] Optionally, the steel node is provided with a terminal, which is located at least 50 mm above the liquid surface of the conductive medium or located below the liquid surface and is sealed to the steel node (3) with insulating tape.
[0014] Secondly, the present invention also provides an accelerated corrosion test method for steel nodes, comprising the following steps: fixing the steel node inside a test tank, arranging an auxiliary electrode inside the test tank, and injecting a conductive medium into the test tank; turning on the power supply electrically connected to the auxiliary electrode and the steel node, and performing the test according to the specified energizing time. The steel nodes were subjected to accelerated corrosion by applying electricity. The power-on time The calculation formula is:
[0015] in The current efficiency coefficient is... For electron transfer number, It is Faraday's constant. The molar mass of iron, For the total applied current, This represents a theoretical loss of quality.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: This application provides an accelerated corrosion testing device for steel nodes. By fixing the centrally symmetrical steel node at the center of the test tank, it divides the node into multiple interconnected regions. A stirring element drives the conductive medium to circulate between these regions, improving the uniformity of ion mass transfer distribution and preventing prolonged adhesion of air bubbles to the node surface. This enhances the uniformity and reliability of the accelerated corrosion test results. Simultaneously, the symmetrical arrangement of auxiliary electrodes helps establish a uniform initial current field around the node, which, in conjunction with the medium flow, suppresses localized current concentration. Through the surrounding electrode layout and the division of the steel node's geometry, this application allows the accelerated corrosion testing device to be specifically adapted to the complex shape of steel nodes from a structural design perspective. It enables uniform accelerated corrosion testing of large steel nodes and is simple and convenient to operate. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] Legend: Figure 1 This is a schematic diagram of the main structure of the present invention; Figure 2 This is a schematic diagram of the structure of the steel node of the present invention fixed inside the test tank; Figure 3 This is a top view of the test tank structure of the present invention; In the figure: 1. Test tank; 2. Power supply; 3. Steel node; 4. Auxiliary electrode; 5. Conductive medium; 6. Stirring component; 7. Magnetic drive component; 8. Insulating pad. Detailed Implementation
[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] It will be understood that although the terms “first,” “second,” “third,” “fourth,” etc., may be used here to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another.
[0021] Combination Figures 1 to 3As shown, an accelerated corrosion testing device for a steel node 3 provided in this embodiment of the invention includes a test tank 1, a steel node 3, an auxiliary electrode 4, a power supply 2, a magnetic drive component 7, and a stirring component 6.
[0022] It should be noted that the steel node 3 can specifically be an X-shaped, K-shaped, T-shaped, or Y-shaped pipe node. The following embodiments all use an X-shaped centrally symmetrical pipe node as a specific example to describe the device structure, component layout, and connection relationships of the present invention in detail. The X-shaped steel node 3 consists of two main pipes arranged in a cross-symmetrical manner, forming four branch pipes extending along the diagonal direction.
[0023] The test tank 1 is a square, open container used to hold the conductive medium 5. A steel node 3 is fixedly positioned at the center of the test tank 1, serving as the specimen to be corroded. Four auxiliary electrodes 4 are arranged on the test tank 1, forming a ring-shaped negative electrode layout. The positive terminal of the power supply 2 is electrically connected to the steel node 3, and the negative terminal is electrically connected to the common terminal of the four auxiliary electrodes 4 connected in parallel. A wooden support frame is provided below the test tank 1, and its bottom space is divided into four quadrants. A magnetic drive unit 7 is installed in each quadrant, and a stirring unit 6 is placed at the center of each quadrant inside the test tank 1.
[0024] The test tank 1 is made of corrosion-resistant material and has a square, open structure. The side length of the test tank 1 is determined based on the horizontal projected area of the steel node 3. Its bottom area must completely enclose the projected area of the steel node 3, and space must be left outside the steel node 3 for the installation of auxiliary electrodes 4 and stirring components 6. After the test tank 1 submerges the steel node 3, the liquid level must meet the submersion requirements and allow for adjustment.
[0025] Before testing, steel node 3 requires surface pretreatment: removing oil, rust, and scale; cleaning and drying; and measuring and recording the initial mass, initial wall thickness, and main geometric dimensions. Based on the potential corrosion locations in the actual project, the surface of steel node 3 is divided into corrosion and non-corrosion zones. Non-corrosion zones, such as the ends of members, clamping points, and wire connections, are sealed with a water-resistant insulating coating, epoxy resin, or silicone rubber. Corrosion zones retain their exposed steel surface.
[0026] The steel node 3 is fixed to the center of the test tank 1 by an insulating pad 8, with its center coinciding with the geometric center of the test tank 1. The steel node 3, placed in the test tank 1, divides the internal space of the test tank 1 into multiple quadrants: the first quadrant, the second quadrant, the third quadrant, and the fourth quadrant, maintaining communication between the conductive medium 5. The insulating pad 8 creates a channel between the bottom of the steel node 3 and the bottom surface of the test tank 1, allowing the conductive medium 5 to circulate throughout the tank for subsequent stirring by the agitator 6. The insulating pad 8 tilts and elevates the steel node 3, causing the upper wiring area of the steel node 3 to protrude at least 50 mm above the surface of the conductive medium 5. Alternatively, it can be sealed to the steel node 3 below the liquid surface using insulating tape. The wiring terminal of the steel node 3 is located in this protruding area. When the steel node 3 is large, two wiring terminals are used. All terminals should use wires of the same material, cross-sectional area, and length, and be connected to the same positive terminal of power supply 2 to ensure equal resistance in each branch and avoid uneven current distribution due to differences in wires. Terminals and exposed wires should be sealed with waterproof insulation material. For steel nodes 3 with intersections, welds, concave corners, or partially obstructed areas, their height and orientation should be adjusted to ensure these critical areas are in full contact with the flowing conductive medium 5.
[0027] Four auxiliary electrodes 4 are fixed to the test tank 1, arranged symmetrically around the steel node 3. The auxiliary electrodes 4 can be made of graphite or copper sheets, and the material, dimensions, and immersion depth of the four auxiliary electrodes 4 are identical. The upper end of each auxiliary electrode 4 is above the designed liquid level of the conductive medium 5, and the lower end is close to the bottom of the test tank 1 but not in direct contact with the bottom. The horizontal distance between the four auxiliary electrodes 4 and the centroid of the steel node 3 is equal, ensuring that the conductive path length from four directions to various parts of the surface of the steel node 3 is consistent. The four auxiliary electrodes 4 are connected in parallel by wires of the same length and cross-sectional area, and are connected to the negative terminal of the power supply 2, forming a four-corner equipotential cathode network. This symmetrical cathode arrangement solves the problem of electric field concentration along the electrode connection direction in traditional single-pair electrode arrangements, suppressing local current concentration.
[0028] Power supply 2 operates in constant current mode. Its positive terminal is connected to the symmetrical terminal of steel node 3 via a wire of equal length, and its negative terminal is connected to the common parallel terminal of the four auxiliary electrodes 4 via a wire of equal length, forming a current-carrying corrosion circuit. The current is determined based on the pre-selected average current density and the surface area of the corrosion region, calculated using the following formula:
[0029] In the formula, For the current flowing through, For current density, This represents the surface area of the corroded region at the steel node.
[0030] The selection of current density must take into account both the test period and the similarity of corrosion morphology: too high a current density will exacerbate oxygen or hydrogen evolution side reactions, leading to sudden changes in surface pH and abnormal dissolution; too low a current density will result in an excessively long test period. The specific value of i is confirmed through preliminary experiments, with the aim of forming a rust layer with a color and texture similar to natural corrosion in the conductive medium 5 used.
[0031] The stirring element 6 is a magnetic stirring rotor, positioned at the center of each quadrant. Inside the test tank 1, one stirring element 6 is placed at a position corresponding to the center of the working disk of each magnetic drive element 7. The four stirring elements 6 are identical in specifications, dimensions, and type, all being cylindrical with joints. This allows for the simultaneous generation of effective axial and radial flow components at lower speeds, avoiding the formation of a single horizontal circulation and facilitating the interweaving flow of the conductive medium 5 between the four quadrants.
[0032] Four magnetic drive units 7 are used in conjunction with wooden strip supports to achieve symmetrical stirring in four quadrants. The wooden strip supports, mounted below the test tank 1, consist of a detachable outer frame and an internal cross-shaped support, dividing the space below the test tank 1 into four quadrants corresponding to the tank's interior. The height of the wooden strip supports is greater than the height of the magnetic drive units 7, allowing each of the four magnetic drive units 7 to be installed in one of the four quadrants. All four magnetic drive units 7 are of the same model, with identical rated power, working disc size, and speed adjustment range. The upper surface of the working disc of each magnetic drive unit 7 is in close contact with the outer bottom surface of the test tank 1 to ensure efficient magnetic coupling. The horizontal distance between the magnetic drive unit 7 and the power supply 2 is no less than 0.5m to prevent the magnetic field generated by the magnetic drive unit 7 from interfering with the electrochemical current field within the test tank 1.
[0033] The selection of the magnetic drive unit 7 and the agitator 6 needs to be quantitatively verified. The maximum agitation capacity of a single magnetic drive unit 7 should meet the following requirements:
[0034] In the formula, This represents the maximum stirring capacity of a single magnetic drive unit. The bottom area of the test tank, This represents the height of the conductive medium liquid level.
[0035] This condition ensures that each magnetic drive unit 7 is capable of driving the entire volume of conductive medium 5 within its corresponding quadrant. The working disk size of the magnetic drive unit 7 should preferably not exceed half the side length of the test tank 1 and be as close to this value as possible, ensuring that the rotation radius of the stirring unit 6 can cover the main area of the quadrant. The four stirring units 6 are located near the center of the four quadrants respectively, and maintain an appropriate distance from the steel node 3, auxiliary electrode 4, and sidewall of the test tank 1 to prevent collisions during rotation.
[0036] The four magnetic drive units 7 are set to the same rotational speed. This enables the conductive medium 5 to form a circulating flow that runs through all four quadrants, reducing the concentration gradient and oxygen concentration difference around the steel node 3, while preventing the generation of strong vortices that would draw in air and form bubbles.
[0037] The symmetrical arrangement of the auxiliary electrodes 4 and the four-quadrant layout of the stirrer 6 are not independent of each other, but rather form a synergistic effect between the electric field and the flow field. The symmetrical arrangement of the auxiliary electrodes 4 ensures the consistency of the driving force for electrochemical reactions at all points of the steel node 3. However, in the static conductive medium 5, even if the initial current field is uniform, as corrosion progresses, differences will still occur in ion concentration, dissolved oxygen content, and the degree of corrosion product accumulation, leading to localized corrosion conditions. The stirrer 6 drives the conductive medium 5 to continuously circulate between multiple regions, making the ion mass transfer conditions, oxygen replenishment rate, and bubble detachment probability more consistent, preventing uneven distribution of secondary current caused by mass transfer differences. If there is only stirring without the symmetrical arrangement of the auxiliary electrodes 4, the flow of the conductive medium 5 can only improve mass transfer, but cannot correct the electric field bias caused by the asymmetry of the electrode positions.
[0038] The accelerated testing apparatus provided in this embodiment has the following working process and testing method: First, the service environment and target corrosion level of steel node 3 are determined. Based on field sampling data from steel node 3 or furnace-tested specimens under the same environment, the target corrosion level is determined. The target corrosion level can be characterized by mass loss rate or wall thickness loss rate, and the theoretical baseline mass loss is calculated accordingly. , Among them, theoretical benchmark quality loss Determine by either of the following two methods: Method 1: Based on the target uniform corrosion depth Corrosion area of steel nodes Calculate theoretical baseline mass loss :
[0039] in, The density of iron, The target uniform corrosion depth is determined based on the wall thickness loss corresponding to the target corrosion degree.
[0040] Method 2: Based on the initial mass of the corroded area of the steel node Corrosion degree of the target Calculate theoretical baseline mass loss :
[0041] in, The target corrosion level is set between 0 and 1 (e.g., 0.30 represents 30%), and is determined by on-site measurements or empirical standards. The initial mass of the corroded part of the steel node before corrosion is obtained by looking up the design drawings or by actual measurement.
[0042] For cases where wall thickness loss is used for evaluation, an ultrasonic thickness gauge is used to measure multiple points on the surface of the sampling area, and the arithmetic mean is taken as the wall thickness after corrosion. The initial wall thickness is determined according to the nominal wall thickness in the design drawings. For cases where mass loss is used for evaluation, the initial mass is obtained according to the design drawings, and the mass after corrosion is obtained by weighing after rust removal. For iron-based steel node 3, the molar mass M is taken as 56 g / mol.
[0043] After completing the pretreatment, sealing, quadrant division, and fixing of steel node 3 as described above, install auxiliary electrode 4 and connect the circuit, and add conductive medium 5 to the liquid level. Start the magnetic drive 7 and adjust it to the predetermined speed, and observe the flow state of conductive medium 5. After the flow field stabilizes and the conductive medium 5 forms a stable cycle through the four quadrants, turn on power supply 2 and apply current in constant current mode.
[0044] The energizing time is calculated according to Faraday's law:
[0045] Among them This is the current efficiency coefficient, with a value ranging from 0.85 to 0.90. For electron transfer number, It is Faraday's constant. The molar mass of iron, For the total applied current, For theoretical mass loss Iron-based steel nodes =2, It is Faraday's constant. =96485 C / mol The molar mass of iron, =56 g / mol.
[0046] Current efficiency coefficient The amount of electricity consumed to correct for side reactions such as hydrogen evolution is measured in the range of 0.85 to 0.90. The method for determining this value is as follows: Before the formal test, a short-term pre-test is conducted using the same steel node material and solution conditions as the formal test. (Using the weight loss method, a small specimen of the same steel node material as the formal test is energized for 2-4 hours under the same solution and current density. The actual corrosion mass loss is obtained by weighing the specimen before and after energization. The theoretical corrosion mass loss under the same amount of electricity is calculated according to Faraday's law. Dividing the actual corrosion mass loss by the theoretical corrosion mass loss yields the current efficiency coefficient.) If a preliminary test cannot be conducted, reference can be made to the electrical corrosion test data of similar marine low-carbon steels in simulated seawater. The value is estimated to be between 0.85 and 0.90. The actual corrosion mass loss will be used to determine the final value after the formal test. The value is validated and corrected.
[0047] Total current From current density With the corroded area The product is determined, that is Current density Depending on the required acceleration rate, the higher the current density, the faster the corrosion rate and the shorter the energizing time.
[0048] During the electro-corrosion process, the pH value of the conductive medium 5 in each area is measured periodically and averaged. When the average value deviates from 7.5~8.5, acidic regulator is added in small amounts multiple times to adjust the pH, while maintaining stirring to ensure uniform diffusion of the regulator. Simultaneously, surface foam and detached corrosion products on the conductive medium 5 are periodically skimmed off, air bubbles adhering to the surfaces of the auxiliary electrode 4 and steel node 3 are removed, and purified water is added to the initial liquid level to compensate for evaporation loss. The operating status of the stirring element 6, the actual output current of the power supply 2, and the insulation condition of the terminals are checked. The ambient temperature is controlled between 15~35℃.
[0049] Once the cumulative energizing time reaches the calculated value, turn off power supply 2. After the current drops to zero, turn off the stirring drive. Remove steel node 3, rinse with deionized water, remove corrosion products according to standard procedures, dry to constant weight, weigh to obtain the post-corrosion mass, and calculate the actual degree of corrosion.
[0050] Finally, it should be noted that the above embodiments are merely specific implementations of the present invention, used to illustrate the technical solutions of the present invention, and not to limit it. The scope of protection of the present invention is not limited thereto. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that any person skilled in the art can still modify or easily conceive of changes to the technical solutions described in the foregoing embodiments within the scope of the technology disclosed in the present invention, or make equivalent substitutions for some of the technical features; and these modifications, changes, or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. All should be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
[0051] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.
Claims
1. An accelerated corrosion testing device for steel joints, characterized in that, include: Test tank (1) contains conductive medium (5); A steel node (3) is fixedly installed inside the test tank (1), and the steel node (3) divides the internal space of the test tank (1) into multiple interconnected areas; An auxiliary electrode (4) is disposed in the test tank (1), and the auxiliary electrode (4) is arranged at intervals from the steel node (3); The power supply (2) is electrically connected to the auxiliary electrode (4) and the steel node (3), respectively; At least one agitator (6) is disposed inside the test tank (1) to drive the conductive medium (5) to circulate between the plurality of regions.
2. The apparatus according to claim 1, characterized in that, The auxiliary electrode (4) includes at least two pieces, which are symmetrically arranged on the inner sidewall of the test tank (1). The height of the auxiliary electrode (4) is not lower than the liquid level of the conductive medium (5).
3. The apparatus according to claim 2, characterized in that, The auxiliary electrodes (4) consist of four pieces, distributed on two opposite inner sidewalls of the test tank (1), with two pieces arranged on each sidewall.
4. The apparatus according to claim 1, characterized in that, The steel node (3) is a centrally symmetrical structure and is fixedly installed at the center of the test tank (1). The steel node (3) divides the internal space of the test tank (1) into four interconnected quadrant regions.
5. The apparatus according to claim 1, characterized in that, The stirring element (6) is positioned at the center of any of the quadrant regions.
6. The apparatus according to claim 1, characterized in that, The stirring component (6) is a magnetic stirring rotor. The device also includes a magnetic drive component (7), which is located below the test tank (1) and cooperates with the magnetic stirring rotor.
7. The apparatus according to claim 6, characterized in that, The horizontal distance between the magnetic drive (7) and the power supply (2) is not less than 0.5m.
8. The apparatus according to claim 1, characterized in that, An insulating pad (8) is provided between the steel node (3) and the bottom of the test tank (1), and a channel is left between the steel node (3) and the bottom of the test tank (1) for the conductive medium (5) to flow.
9. The apparatus according to claim 1, characterized in that, The steel node (3) is provided with a terminal, which is located at least 50 mm above the liquid surface of the conductive medium (5) or below the liquid surface and is sealed to the steel node (3) by insulating tape.
10. A method for accelerating corrosion testing of steel joints, characterized in that, Includes the following steps: The steel node (3) is fixedly installed inside the test tank (1), and an auxiliary electrode (4) is arranged inside the test tank (1). A conductive medium (5) is injected into the test tank (1). The power supply (2) that is electrically connected to the auxiliary electrode (4) and the steel node (3) is turned on, and the power is supplied according to the specified energizing time. The steel node (3) was subjected to accelerated corrosion by electric current; The power-on time The calculation formula is: in The current efficiency coefficient is... For electron transfer number, It is Faraday's constant. The molar mass of iron, For the total applied current, This represents a theoretical loss of quality.